Character Education Based on Local Wisdom: An Analysis of the Modernisation Impact on the Ngayu-ayu Ritual in Sembalun Lombok - Astari, Wiya Mela; Mayasari, Deviana; Saddam, Saddam (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
The community of Sembalun Village preserves profound local wisdom through the Ngayu-ayu ritual, a practice upheld to express gratitude to Allah Almighty. This research aims to analyse the character education values inherent in the Ngayu-ayu ritual and investigate modernisationâ€™s impacts on this cultural tradition. Employing a qualitative research method, key figures from the community, including cultural, religious, youth, and community leaders, were chosen as research subjects through purposive sampling. The Ngayu-ayu ritual encapsulates a diverse array of character education values, encompassing religiosity, communal cooperation gotong-royong), tolerance, national spirit, patriotism, environmental consciousness, responsibility, discipline, and the appreciation of achievements. However, the ritual has undergone substantial changes due to the influence of modernisation. Ritual stages have been abbreviated and sometimes omitted, with a meticulous preservation of the sacrosanct elements. The traditional practice of fetching water from the 13 sacred springs, once undertaken on foot, now involves using vehicular transport. Furthermore, the communal meal-sharing activity known as â€œbegibungâ€ has shifted from a symbolic blessing dispersal to a more pragmatic distribution of surplus food to the local community. The impact of modernisation is apparent not only in altered ritual activities but also in the evolving mindset of the Sembalun community.